2005
DOI: 10.1152/ajpregu.00576.2004
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in apoptosis with disuse atrophy in soleus muscle

Abstract: Muscle atrophy is associated with a loss of muscle fiber nuclei, most likely through apoptosis. We investigated age-related differences in the extent of apoptosis in soleus muscle of young (6 mo) and old (32 mo) male Fischer 344 x Brown Norway rats subjected to acute disuse atrophy induced by 14 days of hindlimb suspension (HS). HS-induced atrophy (reduction in muscle weight and cross-sectional area) was associated with loss of myofiber nuclei in soleus muscle of young, but not old, rats. This resulted in a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
225
2
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(257 citation statements)
references
References 68 publications
25
225
2
5
Order By: Relevance
“…These observations have cast doubts about the involvement of mitochondrial caspase-dependent apoptosis in the pathogenesis of sarcopenia. In contrast, several studies have shown that caspase-independent apoptotic pathways are activated in old age [12,18,50,61]. It was found that translocation of mitochondrial EndoG to the nucleus was increased in the soleus muscle of old rats.…”
Section: The Involvement Of Apoptosis In the Pathogenesis Of Sarcopeniamentioning
confidence: 91%
“…These observations have cast doubts about the involvement of mitochondrial caspase-dependent apoptosis in the pathogenesis of sarcopenia. In contrast, several studies have shown that caspase-independent apoptotic pathways are activated in old age [12,18,50,61]. It was found that translocation of mitochondrial EndoG to the nucleus was increased in the soleus muscle of old rats.…”
Section: The Involvement Of Apoptosis In the Pathogenesis Of Sarcopeniamentioning
confidence: 91%
“…Although this phenomenon is well documented in animal and human studies, the underlying mechanisms leading to sarcopenia remain to be fully elucidated. The contributing mechanism(s) leading to sarcopenia are multi-factorial and may include: denervation and reinnervation of motor units, especially within skeletal muscles composed of a high degree of type II muscle fibers [1][2][3]; an alteration in the hormonal milieu in which anabolic hormone concentrations progressively decline [4,5]; elevated concentrations of inflammatory mediators that are not only associated with disease states, but also occur in healthy older adults [6][7][8][9][10][11][12][13]; and myonuclear loss through apoptotic mechanisms [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The process of nuclear apoptosis has been shown to contribute to skeletal muscle mass losses during disease states [20], periods of inactivity [15,17,19,21], and as a result of aging [14]. The presence of apoptotic nuclei within skeletal myofibers has been welldocumented [18,19,22,23], although the precise signaling mechanisms that result in these nuclear losses are just beginning to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations